Взаємопроникнення елементів народної творчості поляків і євреїв - Гольдберг-Мулькевич, О. (Народна творчість та етнографія, 2008)
The old definition of "ShtetT as the compact Jewish community hermetically isolated from non -Jews needs tole rectified. There were personal relations between the communities and they involved numerous spheres of life. My article is concerned with folk crafts and folk arts; the text is focuses not only on the borrowing of motifs, but also on spreading the knowledge of the differences between Jewish and Polish traditional cultures. Most of Jews were craftsmen. Working for non-Jews they had to accommodate themselves to local tradition and local esthetic, but we can also find some examples of mutual interpenetration. We observe such process in tailoring, jeweler's craft, pottery, carpentry, furniture making, paper-cuts.